U-CHANGE Project: a multidimensional consensus on how clinicians, patients and caregivers may approach together the new urothelial cancer scenario - Bracarda, Sergio; Iacovelli, Roberto; Baldazzi, Valentina; Zucali, Paolo Andrea; Gernone, Angela; Conti, Giario Natale; Pappagallo, Giovanni; Brunelli, Matteo; Bruzzi, Paolo; Fiorini, Edoardo; Magenta, Laura; Diomede, Francesco; et al. (Frontiers in Oncology, 2023)
Introduction Advanced urothelial carcinoma remains aggressive and very hard to cure, while new treatments will pose a challenge for clinicians and healthcare funding policymakers alike. The U-CHANGE Project aimed to redesign the current model of care for advanced urothelial carcinoma patients to identify limitations (“as is” scenario) and recommend future actions (“to be” scenario). Methods Twenty-three subject-matter experts, divided into three groups, analyzed the two scenarios as part of a multidimensional consensus process, developing statements for specific domains of the disease, and a simplified Delphi methodology was used to establish consensus among the experts. Results Recommended actions included increasing awareness of the disease, increased training of healthcare professionals, improvement of screening strategies and care pathways, increased support for patients and caregivers and relevant recommendations from molecular tumor boards when comprehensive genomic profiling has to be provided for appropriate patient selection to ad hoc targeted therapies. Discussion While the innovative new targeted agents have the potential to significantly alter the clinical approach to this highly aggressive disease, the U-CHANGE Project experience shows that the use of these new agents will require a radical shift in the entire model of care, implementing sustainable changes which anticipate the benefits of future treatments, capable of targeting the right patient with the right agent at different stages of the disease.